Mechanisms of Plasma-Seed Treatments as a Potential Seed Processing Technology - Waskow, Alexandra; Howling, Alan; Furno, Ivo (Frontiers in Physics, 2021)
Plasma treatments are currently being assessed as a seed processing technology for agricultural purposes where seeds are typically subjected to pre-sowing treatments to improve the likelihood of timely and uniform germination. The aim of this review is to summarize the hypotheses and present the evidence to date of how plasma treatments affect seeds, considering that there is difficulty in standardizing the methodology in this interdisciplinary field given the plethora of variables in the experimental setup of the plasma device and handling of biological samples. The ever increasing interest for plasma agriculture drives the need for a review dedicated to seeds, which is understandable to an interdisciplinary audience of biologists and plasma physicists. Seeds are the first step of the agricultural cycle and at this stage, the plant can be given the highest probability of establishment, despite environmental conditions, to exploit the genetic potential of the seed. Furthermore, seedlings seem to be too sensitive to the oxidation of plasma and therefore, seeds seem to be the ideal target. This review intentionally does not include seed disinfection and sterilization due to already existing reviews. Instead, a summary of the mechanisms of how plasma may be affecting the seed and its germination and developmental properties will be provided and discussed.